2010
DOI: 10.1007/s10637-010-9419-1
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro comparative study with furyl-1,4-quinones endowed with anticancer activities

Abstract: We describe the biological activity of some furylbenzo- and naphthoquinones (furylquinones) on hepatocarcinoma cells and healthy rat liver slices. The effects of furylquinones on cancer cells (Transplantable Liver Tumor, TLT) were assessed by measuring cell death (membrane cell lysis); intracellular contents of ATP and GSH and the activity of caspase-3 were used to determine the type of cell death. Most of the furylquinones tested (at a concentration of 25 μg/ml) induced caspase-independent cell death but comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Several studies suggested that the quinone group is responsible for the ROS-inducing action. Accordingly, many quinone-containing antitumor agents, such as adriamycin, daunorubicin, actinomycin D, mitomycin C, and trenimon, were shown to mediate DNA strand breaks and cell death via an ROS-dependent mechanism. , Free radicals and highly reactive molecules, including superoxide radicals, hydroxyl radicals, semiquinones, and hydrogen peroxide, were found in cells treated with quinone-containing compounds, and those molecules were proved to induce necrosis . Indeed, menadione, a redox-active naphthoquinone, was shown to induce necrosis by damaging plasma membrane integrity via a free radical mediated process. , In addition, furylquinones underwent an activation process via a redox mechanism causing necrosis in TLT hepatoma cells. , As mentioned earlier, ROS are hypothesized as one of the key factors for necrosis in response to several stimuli, and the quinone moiety is recognized as a radical generator. , To test whether ROS played a role in the renieramycin M and 5- O -acetylated hydroquinone derivative mediated cell deaths, the strong antioxidant N -acetylcysteine (NAC 1 mM) was used. The cells were pretreated with NAC prior to 1 and 2 treatments, and cell viability at 24 h was determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggested that the quinone group is responsible for the ROS-inducing action. Accordingly, many quinone-containing antitumor agents, such as adriamycin, daunorubicin, actinomycin D, mitomycin C, and trenimon, were shown to mediate DNA strand breaks and cell death via an ROS-dependent mechanism. , Free radicals and highly reactive molecules, including superoxide radicals, hydroxyl radicals, semiquinones, and hydrogen peroxide, were found in cells treated with quinone-containing compounds, and those molecules were proved to induce necrosis . Indeed, menadione, a redox-active naphthoquinone, was shown to induce necrosis by damaging plasma membrane integrity via a free radical mediated process. , In addition, furylquinones underwent an activation process via a redox mechanism causing necrosis in TLT hepatoma cells. , As mentioned earlier, ROS are hypothesized as one of the key factors for necrosis in response to several stimuli, and the quinone moiety is recognized as a radical generator. , To test whether ROS played a role in the renieramycin M and 5- O -acetylated hydroquinone derivative mediated cell deaths, the strong antioxidant N -acetylcysteine (NAC 1 mM) was used. The cells were pretreated with NAC prior to 1 and 2 treatments, and cell viability at 24 h was determined.…”
Section: Resultsmentioning
confidence: 99%
“…47,48 In addition, furylquinones underwent an activation process via a redox mechanism causing necrosis in TLT hepatoma cells. 47,49 As mentioned earlier, ROS are hypothesized as one of the key factors for necrosis in response to several stimuli, 30 and the quinone moiety is recognized as a radical generator. 44,50−52 To test whether ROS played a role in the renieramycin M and 5-O-acetylated hydroquinone derivative mediated cell deaths, the strong antioxidant N-acetylcysteine (NAC 1 mM) was used.…”
mentioning
confidence: 91%
“…As part of our study of new quinones with potential antitumor activity [10][11][12][13], we recently reported that some phenylaminopyrimido [4,8-c]isoquinolinequinones (APIQ) and their precursors 1 and 2 have in vitro antitumor activity [14], which is enhanced in the presence of a relevant and well-known reducing agent, i.e., ascorbate [15]. These findings, together with the broad range of antitumor activities observed in the aryl-and alkylaminopyrimido [4,8-c]isoquinolinequinones series, led to the suggestion that the observed biological activity is related to the redox properties of these aminoquinones.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Benites et al., (2011) reported a series of furylbenzo‐ and naphthoquinones (furylquinones) derivatives for caspase‐independent cytotoxicity in rat liver slices.…”
Section: Caspase‐3 Activatorsmentioning
confidence: 99%